National Distance Education University (UNED) and the Virtualization of its Academic Offer. A Rational Analysis of its Implementation - Arnaldo Rodríguez-Espinoza (Universidad Nacional, Costa Rica, 2017)
This article analyses the virtualization process of university courses implemented in the four schools of the National Distance Education University (UNED, for its acronym in Spanish). Primarily, the objective is to determine whether the virtualization of the courses should be the only alternative for students, or if it should be another tool to integrate into the pedagogic model of distance education in the context and reality of Costa Rica, in regards to the viability of access to digital technologies. Thus, an analysis of the Information and Communication Technologies (ICT) was done through virtualization and e-learning, explaining its implementation in UNED, a setting where there is still a long way to go in terms of accessibility, mainly between urban and rural areas. Additionally, the ICTs are approached as an alternative, an option, or a tool within the distance education model, since their implementation depends on a pedagogic foundation (techniques, strategies, and methodologies in ICT), and above all, on the context. The conclusions state that the virtualization of the courses must be an alternative but not an imposition for the students, because consideration of the context is vital, in terms of accessibility to digital technologies in Costa Rica, meaning that the quality of education must prevail over the means (semi-virtual, hybrid, virtual, or distance). Virtualization is not a matter of being at the forefront by means of technical innovation, but its implementation must be based on a real need with suitable conditions (adequate logistic infrastructure). Finally, ICTs must depend on a clearly established pedagogical curriculum, without reducing the access and quality in education.